Socializing Minds, Socializing Bodies: Implications of a View to the Bodily Side of Lenz’s Spinozist Theory of Mind - Andrea Carmen Blättler (Journal of Spinoza Studies, 2023)
Martin Lenz introduces Spinoza to us as a bundle theorist of mind, for whom there cannot be a single finite mind. Since Spinoza conceives of the mind as the idea of the body, a reinterpretation of his theory of mind will have a bodily concurrence. As a corporeal interlude to Lenz’ Spinozist theory of mind, I enquire what follows for the latter if one takes into account more explicitly the structural complexity of the attribute of extension, expressing itself in the plurality and variability of bodies. While Lenz reads Spinoza through a lens of intersubjectivity and parallelism, my reflection leads to the consideration that the plurality and variability of bodies might call for a transindividual rather than an intersubjective account and for conceiving of body and mind as equal rather than parallel. That this complicates Lenz’ account of the identity of the mind over time is an avail rather than a problem. It invites developing Lenz’ reading beyond what the context of his book allows, helping us to navigate the intricate dynamics in which we strive for our bodies to become more capable, our minds more eternal.